Extraction and Characterization of Dye Extract from Bridelia ferruginea - Joshua Yakubu; Andema Aaron Kanadi; Bifam Mathias; Peter Michael Dass (Darul Yasin Al Sys, 2026)
This study investigated the extraction and characterization of a natural dye from the stem of Bridelia ferruginea using the Soxhlet method. The extraction yielded 32% dye extract, which exhibited a maroon color, a pH of 5.10, a melting point of 200–210 °C, a density of 1.20, partial solubility in water, and complete solubility in methanol. Phytochemical screening revealed the presence of alkaloids, glycosides, flavonoids, terpenoids, saponins, tannins, and steroids, whereas phenols and anthraquinones were absent. The dye extract also demonstrated inhibitory activity against certain bacterial and fungal organisms. Characterization using FTIR, UV-Visible spectroscopy, SEM, TGA, and GC-MS further elucidated its properties. FTIR analysis indicated the presence of O–H stretching, C–H stretching, C=C stretching, C–H bending, and C–O stretching functional groups. The UV-Visible spectrum showed distinct absorption peaks, with the most prominent peak observed at 304 nm and an absorbance value of 2.4889. SEM analysis revealed compact, fused, or crystalline-like surface structures. TGA showed thermal stability in three stages, with initial weight loss occurring between 30 and 150 °C, major weight loss between 250 and 450 °C, and residual mass remaining above 500 °C. GC-MS analysis identified 18 compounds with different retention times and intensities, among which maltose showed the highest intensity (2.50), while propanoic acid and tetral glycol showed lower intensities (0.20). These findings demonstrate that the stem extract of Bridelia ferruginea possesses notable physicochemical, phytochemical, antimicrobial, and structural characteristics relevant to its potential use as a natural dye.